Autonomy to a fault: The confluence of organ donation, euthanasia, and the dead donor rule. (27th January 2023) - Rubin, Jonah
Abstract: Five countries now permit organ donation after euthanasia, on the basis of respecting donor autonomy. Some now openly consider performing euthanasia itself via organ extraction to better preserve organ viability, albeit in violation of the dead donor rule. Proponents argue that respect for patient autonomy requires this option; the dead donor rule is inapplicable since it fulfills donors' wishes. Other ethical arguments, not addressed herein, explore issues including dying at home, impact on clinicians, and societal faith in donation enterprise, but these concerns are not insurmountable. This paper instead solely critiques proponents' oversimplified understanding of autonomy with an autonomy‐based argument against any linkage of organ donation and euthanasia, regardless of its timing. Respect for patient autonomy does not unilaterally require fulfilling patients' every wish. Moreover, the very possibility of organ donation with euthanasia limits donor autonomy qualitatively and quantitatively substantially more than by offering it. In fact, organ donation after euthanasia violates the purpose of the dead donor rule, even if not its technicalities.